Short-term and long-term impact of diagnosed and undiagnosed chronic obstructive pulmonary disease on coronary artery bypass grafting surgery. Issue 1158 (12th January 2021) - Gatta, Francesca; Haqzad, Yama; Loubani, Mahmoud
Abstract : Objectives: This study sought to compare clinical outcomes between three categories of patients: non-chronic obstructive pulmonary disease (COPD), diagnosed COPD and undiagnosed COPD in coronary artery bypass grafting surgery. Methods: A single-centred retrospective study from January 2010 to December 2019. Primary outcomes were postoperative complications, length of ITU admission and in-hospital staying. Secondary outcomes were reintervention rate, in-hospital and long-term mortality. Results: A total of 4020 patients were analysed and divided into three cohorts: non-COPD (group A) (74.55%, n=2997), diagnosed COPD (group B) (14.78%, n=594) and undiagnosed COPD (group C) (10.67%, n=429). The rate of respiratory complications was noted in this order: group B>group C>group A (p 0.00000002). Periooperative acute kidney injury and wound complications were higher in group B (p 0.0004 and p 0.03, respectively). Prolonged in-hospital staying (days) resulted in group B (p 0.0009). Finally, long-term mortality was statistically higher in group B and C compared with group A (p 0.0004). No difference in long-term mortality was noted in relation to the expected FEV1% in group B (p 0.29) and group C (p 0.82). Conclusions: In CABG surgery, COPD is a well-known independent risk factor for morbidity. Patients with preoperative spirometry results indicative of COPD result in the same outcomes of known patients with COPD. As a result of that, greater value should be given to the preoperative spirometry in the EuroSCORE. Finally, the expected FEV1% appears not be a predictor for long-term survival.